Descriptors for brassica and raphanus - International Board for Plant Genetic Resources; European Commission (International Board for Plant Genetic Resources, 1990)
Brassica and Raphanus spp, are highly polymorphic, exhibiting a wide range of intraspecific variation and utilization. Similar morphotypes exist among several species. The descriptors and descriptor states used in this document have been selected from extensive lists of descriptors prepared by crop experts in various countries. Descriptors have been selected to provide the characterization and preliminary evaluation of the rangeof discrete morphotypes and intergrading morphotypes found in most of the Brassica species and Raphanus. The system is also sufficiently flexible as to accommodate the characterization of wild and weedy species. The greatest variety of descriptor states exists for the mature vegetative state of the various morphotypes. Therefore, for some morphotypes certain desccriptor states will not be applicable and therefore omitted from use, e.g. descriptors for root characteristics would not be used for heading or large stemmed morphotypes, nor would many of the vegetative descriptors be of value in characterizing or evaluating oilseed forms.